Richard III - Shakespeare, William, 1564-1616.; Raffel, Burton; Bloom, Harold (New Haven : Yale University Press, 2008)
Treacherous, power-hungry, untempered by moral restraint, and embittered by physical deformity, Richard, the younger brother of King Edward IV, is ablaze with ambition to take England's throne. Richard III, Shakespeare's long chronicle of Richard's machin.
""Table of Contents""; ""About This Book""; ""Introduction""; ""Some Essentials of the Shakespearean Stage""; ""Richard III""; ""An Essay by Harold Bloom""; ""Further Reading""; ""Finding List""
Includes bibliographical references (pages 201-206) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Richard -- III, -- King of England, -- 1452-1485 -- Drama; Richard -- III, -- King of England, -- 1452-1485; Great Britain -- History -- Richard III, 1483-1485 -- Drama; LITERARY CRITICISM -- Shakespeare; DRAMA -- Shakespeare; DRAMA -- General; Great Britain; English Literature; English; Languages & Literatures; 1483-1485; Drama; History